LIQUID CRYSTAL COMPOSITION AND LIQUID CRYSTAL DISPLAY DEVICE - SAITO MASAYUKI; FURUSATO YOSHIMASA; KURIHARA ERIKO (2013)
To provide a liquid crystal composition satisfying at least one of characteristics such as a high maximum temperature of a nematic phase, a low minimum temperature of the nematic phase, a small viscosity, a suitable optical anisotropy, a large negative dielectric anisotropy, a large specific resistance, a high stability to ultraviolet light and a high stability to heat, and so forth. To provide an AM device having a short response time, a large voltage holding ratio, a large contrast ratio, a long service life and so forth. The liquid crystal composition contains a specific compound having a polymerizable group as a first component and a specific compound having a large negative dielectric anisotropy and a low minimum temperature as a second component, and may contain a specific compound having a small viscosity or a large maximum temperature as a third component, and a liquid crystal display device includes the composition.